Synthesis, characterization, and thermoelectric properties of poly(p-phenylenediamine)/poly(sulfonic acid diphenyl aniline) composites - Huner, Keziban (WILEY, 2022)
Thermoelectric materials are of great importance as they are materials that can convert even a small waste heat in the environment into electrical energy. Today, interest in polymeric thermoelectric materials, which are low in cost, abundant in raw materials, and easy to process, has increased. In this study, PpPD, PSDA, and PpPD/PSDA composites were synthesized in aqueous medium by a simple method by chemical oxidative polymerization. The thermoelectric properties of the polymers were investigated and the PSDA ratio in the composite increased from 10% to 50%, while the Seebeck coefficient increased approximately 5 times from 70 mu V/K to 340 mu V/K. The highest Seebeck coefficient and power factor were obtained from PpPD/PSDA3 composite as 340 mu V/K and 3.5 x 10(-3) mu W/mK(2), respectively. It was observed that PpPD/PSDA composites had better thermoelectric properties and thermal stability than PpPD and PSDA.
Keywords: clean energy; Seebeck coefficient; thermoelectric; METAL-ION SORPTION; OXIDATIVE COPOLYMERIZATION; POWER-FACTOR; PERFORMANCE; PHENYLENEDIAMINE; MICROPARTICLES; NANOPARTICLES; CONDUCTIVITY; OPTIMIZATION; POLYMERS; Engineering; Polymer Science